Screening Mentally Retarded Children for Inborn Errors of Metabolism - Shreevastava, Naveen K.; Pandey, Arti S. (Journal of Nepal Health Research Council, 2017)
Background: Most inborn errors of metabolism result in mental retardation and death due to accumulation of abnormal metabolites in the tissues. The presence of abnormal metabolites in the urine of mentally retarded individuals has been used worldwide for detection of inborn errors of metabolism. The purpose of the study is to determine the prevalence of inborn error of metabolism in mentally retarded children. Methods: Random urine samples were collected from mentally retarded children at two institutes in Kathmandu, and also from 60 normal children from Duwakot, Nepal after obtaining consent from their parents. Urine was then tested for the presence of amino acids, keto-acids, mucopolysaccharides, fructose, glucose and protein using simple qualitative color reactions in the laboratory. Results: The tests detected eight cases of Phenylketonuria, which turned out to be false positive on paper chromatography. Three cases of presence of ketone bodies (acetoacetate), ten cases of α-ketoaciduria, two cases of mucopolysaccharidosis and twelve cases of fructosuria amongst the sixty-two urine samples were also found. Conclusions: Certain aminoacidurias, ketoacidurias and mucopolysaccharidoses might be present in the Nepalese population. Within consideration of errors, the samples tested positive should be evaluated by a higher end method to confirm the utility of these simple and cheap chemical tests.